Partial trisomy 8 mosaicism not detected by cultured amniotic-fluid cells - Meng-Che Tsai; Hsueh-Yin Cheng; Mei-Tsz Su; Ming Chen; Pao-Lin Kuo (Elsevier, 2014)
Objective: Prenatal detection of trisomy 8 mosaicism can be misleading and remains challenging in genetic counseling. Identifying cases of partial or complete trisomy 8 mosaicism will highlight the pitfalls of conventional karyotyping in prenatal amniocentesis for partial or complete trisomy 8 mosaicism. Case report: The patient was born uneventfully at term to a healthy 34-year-old mother. Analysis of the amniotic fluid (AF) cells showed a normal male karyotype. At birth, the newborn presented dysmorphic features, including asymmetric mandibles and ears, anteverted nostrils with a relatively long philtrum, retrognathia, and a clenched hand on the left side. Imaging studies revealed agenesis of the corpus callosum with bilateral colpocephaly, a common arterial trunk bifurcating into the left subclavian and carotid arteries, and bilateral pelviectasis. Cytogenetic analysis of the blood revealed mosaicism of partial trisomy 8: 47,XY,+del(8) (q21.3) [8]/46,XY [12]. Array comparative genomic hybridization (array-CGH) revealed 82.9 Mb duplications at chromosome 8p23.3-8q21.3 with dosage variations. Interphase fluorescence in situ hybridization analysis of urine sediments and buccal smears were compatible with mosaic compositions. A small colony of AF cells was found to have partial trisomy 8 in repeated analysis. Conclusion: Conventional karyotyping through amniocentesis has limitations particularly in detecting rare trisomy mosaicism if trisomic cells show growth disadvantage. Array-CGH using uncultured cells may be of help in providing more information on genetic dosage variations in such cases.